Neuroticism as Mediator and Moderator Between War Atrocities and Psychopathology in Syrian Refugee Children and Adolescents - Khamis, Vivian (Frontiers in Psychology, 2022)
Background: Despite the extensive research on war atrocities and risk factors for psychopathology, there is a paucity of research on the potential mediating and moderating effect of neuroticism in refugee children and adolescents. Objective: This study aimed to analyze whether neuroticism mediated and /or moderated the relationship between war atrocities and different types of psychopathology in Syrian refugee children and adolescents who resettled in Lebanon and Jordan. Participants and Setting: Participants were 1000 Syrian refugee children and adolescents of both sexes. Methods: Questionnaires were administered in an interview format with children at school by two trained psychologists. Descriptive statistics and inter-correlations among variables were used Then the mediator and moderator effect of neuroticism in the relationship between war atrocities and posttraumatic stress, emotion regulation and behavioral and emotional disorders were examined. Results: A partial mediating effect of neuroticism on PTSD, emotion dysregulation, and emotional and behavioral disorders was revealed. Findings also indicated full moderating effects of neuroticism on PTSD as well as partial moderating effects on emotion dysregulation, and emotional and behavioral. Conclusions: Findings contribute to the neuroticism literature by showing that high-N children develop more problems that are psychopathological and have more severe affective reactions to war atrocities in post- resettlement contexts. Early interventions aimed to reduce neuroticism might contribute to a better prognosis in refugee children at high-risk for psychological disorders.